2022
DOI: 10.5755/j02.mech.31499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Machining Parameters on Electrochemical Multi-Field Coupling

Abstract: Electrochemical machining involves three couplings between electric field, flow field and thermal field. The precipitation of hydrogen on the surface of the cathode will affect the entire electrochemical machining process and the final machining quality of the workpiece. Finite element software is used to analyze the effects of different voltages, electrolyte inlet pressure and interelectrode gap on current density, hydrogen volume fraction, conductivity and temperature distribution in this article. The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Mishra Technology studied the cathode structure based on the ow eld simulation model of transverse groove ECM, and concluded that symmetrical and uniform placement of cathode holes can improve the gap ow eld homogeneity [17]. In order to improve the forming accuracy, scholars have established a multiphysical eld coupling model of uid-electric-temperature structure to explore the variation law of electrolyte velocity and bubble distribution in the gap ow eld [18][19][20][21][22]. In the aspect of inner spiral parts with large aspect ratio process test, Mahdavinejad designed and optimized the cathode of small caliber gun barrel ri ing and carried out experimental research [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mishra Technology studied the cathode structure based on the ow eld simulation model of transverse groove ECM, and concluded that symmetrical and uniform placement of cathode holes can improve the gap ow eld homogeneity [17]. In order to improve the forming accuracy, scholars have established a multiphysical eld coupling model of uid-electric-temperature structure to explore the variation law of electrolyte velocity and bubble distribution in the gap ow eld [18][19][20][21][22]. In the aspect of inner spiral parts with large aspect ratio process test, Mahdavinejad designed and optimized the cathode of small caliber gun barrel ri ing and carried out experimental research [23].…”
Section: Introductionmentioning
confidence: 99%